Peran Media dalam Membangun Dialog Antar Budaya di Era Globalisasi - Nirra Fatmah; Fitri Nihayatul Chusna (Universitas Islam Tribakti Lirboyo Kediri, 2025)
One of the goals of national education is character formation, especially in Islamic education, which emphasizes the formation of religious character. In the midst of globalization and modernization that bring significant challenges to student morality, religious character education is becoming increasingly important. MIN 1 Kota Kediri, as a faith-based primary educational institution, strives to instill religious values through the consistent application of a religious culture. However, the success of implementing this culture is greatly determined by the way the head of the madrasah leads. This research arises from the urgency to understand how the participatory leadership of the madrasah head can support the development of students' religious character through religious culture. The method used in this study is a qualitative approach with a case study type. Data collection techniques include non-participatory observation, in-depth interviews with the head of the madrasah, teachers, and students, as well as documentation. Data analysis is conducted using the Miles and Huberman model, which involves the processes of data reduction, data presentation, and conclusion drawing. The validity of the data is ensured through source triangulation, increasing diligence, and data confirmation with informants (member checking). The objectives of this study include describing and analyzing the implementation of the head of the madrasah's participative leadership in developing students' religious character through religious culture at MIN 1 Kota Kediri. The results of the study indicate that the Head of MIN 1 Kota Kediri Madrasah applies participative leadership in the context of a bureaucratic state madrasah, while still allowing room for participation from teachers, staff, and committees in designing religious programs. This contextualization reflects flexibility and collective awareness of the importance of developing religious character. Its implementation is apparent in joint decision-making, fostering religious activities such as dhuha prayers, tadarus, and memorization of juz amma, as well as regular evaluations. This leadership fosters a vibrant religious culture and nurtures students’ character to be religious, disciplined, and of good morals.